Endoscopic Transcortical Transventricular Colloid Cyst Excision — Our Experience (Bangladesh Journal of Neurosurgery, 2020)
Background: Colloid cyst of the third ventricle is a tumour arising from the roof of the third ventricle at the foramen of Monro. Endoscopic excision of colloid cyst is well established technique. There is less morbidity in comparison to the microsurgical resection.Materials and method: Seven patients with colloid cyst were treated with endoscopic excision. Of these five were males and two were female patients. Age ranged thirty to fifty five years from a period from Jan 2016 to Mar 2019 in NINS&H.Results: Most patients had signs of raised intracranial pressure before surgery. Six patients needed post operative VP shunt. Some patients had contusion of the fornix but did not have any memory impairment. Five patients had remnant but there was no symptoms after surgery.Conclusion: Endoscopic excision of the colloid cyst is a good option. Total removal of the tumour is the goal but little remnant of the tumour attached to the tela choroidae is accepted. One year follow-up showed no recurrence of the cyst.Bang. J Neurosurgery 2020; 9(2): 94-98